Acid and alkali resistant fused block, preparation method and application thereof

CN122897599APending Publication Date: 2026-10-13FOSHAN DONGPENG CERAMICS CO LTD +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611406684.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]针对上述缺陷,本发明的目的在于提出一种耐酸碱熔块及其制备方法、应用,解决现有抛釉砖耐酸碱性能不足,且不适应快烧工艺的问题

Benefits of technology

1.耐酸碱熔块成分促使熔体中优先生成结构致密的硼氧四面体,从根本上克服传统硼氧三面体易被腐蚀的缺陷。在结构完整性方面,硼氧四面体中的硼原子与4个氧原子以强共价键结合,形成无悬键的三维对称致密网络,不存在三面体的疏松平面结构与缺电子空轨道;在耐酸机理方面,四面体轨道配位饱和,形成电性与物理屏障,有效阻隔酸性环境中H+的靠近与攻击;在耐碱机理方面,四面体具备较高的电荷密度与饱和结构,对碱性环境中的OH-产生强烈的电性排斥,避免三面体因结合OH-而导致的网络断裂与溶解,从而赋予熔块优异的耐酸碱性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of ceramic glaze, and discloses an acid-alkali-resistant frit, a preparation method and application thereof, raw materials of the acid-alkali-resistant frit include, in terms of mass parts, boron magnesium powder 25-35 parts, potassium feldspar 37-53 parts, zinc borate 1-3 parts, spodumene 5-15 parts, zirconium oxide 4-8 parts, cerium oxide 1-3 parts and aluminum hydroxide 3-7 parts; and according to a mass ratio, the total amount of the boron magnesium powder and the zinc borate is greater than 26% of the raw materials of the acid-alkali-resistant frit, the total amount of the boron magnesium powder and the zinc borate: the total amount of the potassium feldspar and the spodumene = 0.4-0.9:1, and in the chemical composition of the acid-alkali-resistant frit, the mass percentage of boron oxide is greater than or equal to 8.4%, the mass percentage of zinc oxide is greater than or equal to 0.4%, and the mass percentage of cerium oxide is greater than or equal to 1%. The acid-alkali-resistant frit of the application promotes the preferential generation of boron-oxygen tetrahedron with compact structure in a melt, fundamentally overcomes the defect that a traditional boron-oxygen trihedron is easy to be corroded, and thus excellent acid-alkali resistance of the frit is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic glaze technology, and in particular to an acid and alkali resistant frit, its preparation method, and its application. Background Technology

[0002] Polished glazed tiles are widely used in architectural decoration due to their high surface gloss and rich textures. According to the latest national standard GB / T45817-2025 "Consumer Product Quality Classification of Ceramic Tiles" 5A requirement, extremely high standards are set for the acid and alkali resistance of ceramic tile surfaces. However, in actual production and use, the acid and alkali resistance of existing polished glazed tiles often fails to consistently reach Grade A, especially in alkali resistance. Insufficient corrosion resistance can lead to problems such as loss of gloss, matte finish, whitening, and the formation of stubborn stains when exposed to daily acid and alkaline cleaning agents or environmental media, severely damaging their decorative effect and service life.

[0003] To improve the chemical corrosion resistance of polished enamel, existing technologies typically employ the following improvement measures: 1. Glaze formulation modification: Add nanomaterials such as titanium dioxide, zinc oxide, aluminum oxide, and graphene oxide to the glaze formulation in an attempt to form a stable inert layer on the glaze surface to improve chemical stability; 2. Firing process adjustment: A high-temperature slow firing process above 1200℃ is adopted, and the high-temperature holding time is extended in order to reduce the porosity of the glaze layer and promote the formation of a dense composite phase structure in the glaze layer.

[0004] However, the aforementioned existing solutions have significant drawbacks in practical industrial application: First, adding nanomaterials or large amounts of high-temperature corrosion-resistant oxides (such as alumina, titanium dioxide, and silicon dioxide) easily leads to poor glaze sintering performance, resulting in increased pores, decreased transparency, or abnormal coloring after firing. More seriously, these solutions are unstable and costly. Although an inert layer may form on the sintered surface, it is removed during subsequent polishing, exposing the unfixed active oxides (such as free potassium oxide and sodium oxide), making the polished glaze highly susceptible to acid and alkali corrosion. Second, using a high-temperature slow-firing process above 1200℃ significantly prolongs the kiln firing cycle, increases energy consumption, and severely reduces production line output, failing to meet the current green production requirements of the ceramic industry for low-carbon and energy-saving processes. Summary of the Invention

[0005] To address the aforementioned shortcomings, the present invention aims to propose an acid and alkali resistant frit, its preparation method, and its application, thereby solving the problems of insufficient acid and alkali resistance and unsuitability for rapid firing processes in existing glazed bricks.

[0006] To achieve this objective, the present invention adopts the following technical solution: An acid and alkali resistant frit, by mass, comprises the following raw materials: 25-35 parts boron magnesium powder, 37-53 parts potassium feldspar, 1-3 parts zinc borate, 5-15 parts spodumene, 4-8 parts zirconium oxide, 1-3 parts cerium oxide, and 3-7 parts aluminum hydroxide; and by mass ratio, the total amount of boron magnesium powder and zinc borate : the total amount of potassium feldspar and spodumene = 0.4-0.9:1. In the chemical composition of the acid and alkali resistant frit, by mass percentage of the oxides of these elements, boron oxide ≥ 8.4%, zinc oxide ≥ 0.4%, and cerium oxide ≥ 1%.

[0007] A method for preparing acid and alkali resistant frit, used to prepare the above-mentioned acid and alkali resistant frit, includes the following steps: mixing the raw materials for the acid and alkali resistant frit, placing them in a furnace, heating them to the highest frit firing temperature of 1500~1560℃, holding them at that temperature for 30~40 minutes, then quenching them in water, crushing and ball milling the quenched frit, passing it through a 100~250 mesh sieve to collect the sieve material, drying it, and obtaining the acid and alkali resistant frit.

[0008] An acid and alkali resistant glaze, by mass parts, comprises: 6-10 parts kaolin, 10-26 parts quartz, 2-6 parts zinc oxide, and 53-87 parts of the above-mentioned acid and alkali resistant frit, wherein, in the chemical composition of the acid and alkali resistant glaze, zinc oxide is ≥2.2% by mass percentage of the oxide of the element.

[0009] Preferably, the quartz particle size is 8000~10000 mesh.

[0010] A method for preparing an acid and alkali resistant glaze, comprising the following steps: mixing the raw materials for the acid and alkali resistant glaze, ball milling them, and passing the material through a 100-250 mesh sieve to obtain the sieve material, thereby obtaining the acid and alkali resistant glaze.

[0011] A method for preparing acid and alkali resistant glazed bricks, using the above-mentioned acid and alkali resistant glaze, includes the following steps: applying the acid and alkali resistant glaze to the surface of the brick blank, sending it into a kiln for firing, raising the temperature to the highest glaze firing temperature of 1140~1160℃, holding it at that temperature for 5~8 minutes; then cooling it, and after polishing and waxing, obtaining acid and alkali resistant glazed bricks.

[0012] Preferably, the firing temperature rise curve is as follows: room temperature - 600℃, heating time 17~19 minutes; 600~1050℃, heating time 8~9 minutes; 1050℃~the highest glaze firing temperature, heating time 4~5 minutes, holding at the highest glaze firing temperature for 6~7 minutes, with a total firing time of 35~40 minutes.

[0013] Preferably, the cooling step is as follows: after firing, the temperature is reduced to 650°C for 5-8 minutes, and then naturally cooled to room temperature.

[0014] An acid and alkali resistant glazed tile is prepared by the above-mentioned preparation method, and the chemical corrosion resistance of the glaze is GLA grade and GHA grade.

[0015] The technical solution provided by this invention may include the following beneficial effects: 1. The acid and alkali resistant frit composition promotes the preferential formation of dense boron-oxygen tetrahedra in the melt, fundamentally overcoming the corrosion susceptibility of traditional boron-oxygen trihedrons. Regarding structural integrity, the boron atoms in the boron-oxygen tetrahedra are strongly covalently bonded to the four oxygen atoms, forming a three-dimensional symmetrical dense network without dangling bonds, eliminating the loose planar structure and electron-deficient empty orbitals of the trihedron. Regarding acid resistance, the tetrahedral orbitals are coordinated to saturation, forming both electrical and physical barriers, effectively blocking H+ in acidic environments. + The approach and attack; in terms of alkali resistance mechanism, the tetrahedron possesses a high charge density and saturated structure, which is resistant to OH- in alkaline environments. - This generates strong electrorepulsion, preventing the trihedron from binding with OH groups. - The resulting network breakage and dissolution endow the fused block with excellent acid and alkali resistance.

[0016] 2. By introducing a large amount of boron magnesium powder and zinc borate as sources of boron oxide, and combining them with raw materials rich in free oxygen such as potassium feldspar and spodumene, high-temperature pre-fabricated briquettes were successfully prepared, overcoming the thermodynamic limitation of the natural preference of high-boron systems for forming boron-oxygen trihedrons. These raw materials were melted at 1600℃, artificially creating a briquette rich in alkali metal / alkaline earth metal ions (such as Li). + K + Mg 2+ The closed oxygen-rich reaction field; under this high temperature environment, boron atoms are surrounded by a large amount of free oxygen and are forcibly bound to oxygen atoms, efficiently transforming into boron-oxygen tetrahedra with better acid and alkali resistance; with the subsequent cooling process, the three-dimensional network of tetrahedra is completely locked in the glassy structure, ensuring the high corrosion resistance matrix of the fused product.

[0017] 3. K in the molten metal + / Na + As a network modifier, it provides free oxygen and, while transforming boron trihedrons into tetrahedrons, is itself fixed in the gaps of the network framework near the tetrahedrons. This anchoring state reduces the porosity of the glass network on the one hand, and prevents alkali metal ions from being easily absorbed by external corrosive media (especially H+ in acids). + The displacement loss significantly reduces the corrosion rate. At the same time, by controlling the amount of alkali metal, the dealkali collapse and alkali corrosion dissolution caused by excessive free alkali suspended in the gaps are avoided, and the free alkali that is originally prone to corrosion is transformed into a stabilizing factor that strengthens the skeleton.

[0018] 4. By synergistically introducing zirconium oxide and cerium oxide, acid and alkali resistance is further enhanced. Zirconium oxide mainly plays a role in acid and alkali resistance. During sintering, it precipitates nano / micron-sized high-hardness inert crystals, such as zircon crystals or tetragonal zirconium oxide, which physically pins cracks and hinders their propagation. At the same time, zirconium ions form a dense ZrO2·nH2O gel passivation film or zirconate layer in situ at the acidic interface, physically isolating H. + Penetration; cerium oxide mainly achieves resistance to alkali and high-temperature corrosion, utilizing Ce 3+ / Ce 4+ Reversible variable valence sacrifice corrosion inhibitor consumption OH - It rapidly adsorbs oxygen and water molecules from the environment through the generated oxygen vacancies, forming a cerium-rich hydroxylated protective layer on the surface with self-adaptive capabilities. After damage, it can quickly and dynamically reorganize, significantly enhancing the overall corrosion resistance and durability of the molten block.

[0019] 5. In the glaze formulation, the amounts of acid and alkali resistant frit and quartz are balanced to ensure acid and alkali resistance. Using 8000-10000 mesh quartz allows for better melting, more complete reaction of ultrafine powder, and significantly reduces the porosity and microcracks of the glaze layer, forming a denser, continuous glassy phase. For polished glazed tiles, higher density results in stronger chemical durability and superior acid and alkali resistance.

[0020] 6. By utilizing the excellent low-temperature rapid firing adaptability of acid and alkali resistant glazes, a non-porous, highly dense polished glaze surface with excellent acid and alkali resistance can be formed under a rapid firing regime, which significantly improves production efficiency and reduces energy consumption.

[0021] 7. The acid and alkali resistant glazed tiles prepared by this invention have GLA level resistance to low concentration acids and alkalis and GHA level resistance to high concentration acids and alkalis, meeting the AAAAA level requirements for chemical corrosion resistance in GB / T 45817-2025 "Ceramic Tiles for Consumer Product Quality Classification". Detailed Implementation

[0022] To facilitate understanding of the present invention, a more complete description is provided below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.

[0023] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0025] An acid and alkali resistant frit, by mass, comprises the following raw materials: 25-35 parts boron magnesium powder, 37-53 parts potassium feldspar, 1-3 parts zinc borate, 5-15 parts spodumene, 4-8 parts zirconium oxide, 1-3 parts cerium oxide, and 3-7 parts aluminum hydroxide; and by mass ratio, the total amount of boron magnesium powder and zinc borate is greater than 26% of the raw materials of the acid and alkali resistant frit, and the ratio of the total amount of boron magnesium powder and zinc borate to the total amount of potassium feldspar and spodumene is 0.4-0.9:1. In the chemical composition of the acid and alkali resistant frit, by mass percentage of the oxides of the elements, boron oxide ≥ 8.4%, zinc oxide ≥ 0.4%, and cerium oxide ≥ 1%.

[0026] The acid and alkali resistant frit composition of this invention promotes the preferential formation of dense boron-oxygen tetrahedra in the melt, fundamentally overcoming the corrosion susceptibility of traditional boron-oxygen trihedrons. Regarding structural integrity, the boron atoms in the boron-oxygen tetrahedra are strongly covalently bonded to the four oxygen atoms, forming a dangling bond-free, three-dimensional symmetrical, dense network, free from the loose planar structure and electron-deficient empty orbitals of the trihedrons. In terms of acid resistance, the tetrahedral orbitals are coordinated to saturation, forming electrical and physical barriers that effectively block H+ in acidic environments. + The approach and attack; in terms of alkali resistance mechanism, the tetrahedron possesses a high charge density and saturated structure, which is resistant to OH- in alkaline environments. - This generates strong electrorepulsion, preventing the trihedron from binding with OH groups. - The resulting network breakage and dissolution endow the fused block with excellent acid and alkali resistance.

[0027] By introducing a large amount of boron-magnesium powder and zinc borate as sources of boron oxide, and combining them with raw materials rich in free oxygen such as potassium feldspar and spodumene, high-temperature pre-fabricated briquettes were successfully prepared, overcoming the thermodynamic limitation of the natural preference for forming boron-oxygen trihedrons in high-boron systems. These raw materials were melted at 1600℃, artificially creating a briquette rich in alkali metal / alkaline earth metal ions (such as Li). + K + Mg 2 + The closed oxygen-rich reaction field; under this high temperature environment, boron atoms are surrounded by a large amount of free oxygen and are forcibly bound to oxygen atoms, efficiently transforming into boron-oxygen tetrahedra with better acid and alkali resistance; with the subsequent cooling process, the three-dimensional network of tetrahedra is completely locked in the glassy structure, ensuring the high corrosion resistance matrix of the fused product.

[0028] K in the molten metal+ / Na + As a network modifier, it provides free oxygen and, while transforming boron trihedrons into tetrahedrons, is itself fixed in the gaps of the network framework near the tetrahedrons. This anchoring state reduces the porosity of the glass network on the one hand, and prevents alkali metal ions from being easily absorbed by external corrosive media (especially H+ in acids). + The displacement loss significantly reduces the corrosion rate. At the same time, by controlling the amount of alkali metal, the dealkali collapse and alkali corrosion dissolution caused by excessive free alkali suspended in the gaps are avoided, and the free alkali that is originally prone to corrosion is transformed into a stabilizing factor that strengthens the skeleton.

[0029] Furthermore, the acid and alkali resistance is further enhanced by synergistically introducing zirconium oxide and cerium oxide. Zirconium oxide mainly plays a role in acid and alkali resistance. During sintering, it precipitates nano / micron-sized high-hardness inert crystals, such as zircon crystals or tetragonal zirconium oxide, which physically pin and prevent crack propagation. At the same time, zirconium ions form a dense ZrO2·nH2O gel passivation film or zirconate layer in situ at the acidic interface, physically isolating H. + Penetration; cerium oxide mainly achieves resistance to alkali and high-temperature corrosion, utilizing Ce 3+ / Ce 4+ Reversible variable valence sacrifice corrosion inhibitor consumption OH - It rapidly adsorbs oxygen and water molecules from the environment through the generated oxygen vacancies, forming a cerium-rich hydroxylated protective layer on the surface with self-adaptive capabilities. After damage, it can quickly and dynamically reorganize, significantly enhancing the overall corrosion resistance and durability of the molten block.

[0030] In the frit formulation, the mass ratio of (magnesium boron powder + zinc borate) to (potassium feldspar + spodumene) is 0.4~0.9. If it is higher than 0.9, there is an excess of boron, resulting in too many boron-oxygen trihedrons due to a lack of potassium. + / Na + The free oxygen provided by Li cannot be converted into boron-oxygen tetrahedra. If there is an excess of boron-oxygen trihedra, the acid and alkali resistance of the glaze decreases; if it falls below 0.4, then K... + / Na + / Li excess, with too much free K + / Na + / Li cannot bind boron-oxygen tetrahedra, and the acid and alkali resistance of the glaze will be greatly reduced.

[0031] The overall content of boron magnesium powder and zinc borate ensures that the frit has an appropriate amount of boron-oxygen tetrahedra. If the content is too low, the amount of boron-oxygen tetrahedra generated will be insufficient, resulting in insufficient acid and alkali resistance of the frit; if the content is too high, it will provide K + / Na + / Li + The content of additives should also be increased accordingly, but excessive additives will cause the melting point of the frit to be too low, which will lead to over-firing of the glaze and defects such as blistering and glaze flow in the glaze layer.

[0032] Zirconia, cerium oxide, and aluminum hydroxide have relatively high melting temperatures. Maintaining this content range allows for adjustment of the molten block temperature. Furthermore, as chemically resistant oxides, zirconia, cerium oxide, and aluminum oxide can significantly improve acid and alkali corrosion resistance when introduced. If the content is too low, the acid and alkali resistance will deteriorate; if it is too high, the transparency of the glaze will decrease.

[0033] Aluminum hydroxide is selected as the aluminum source. Aluminum hydroxide decomposes into highly active, ultrafine amorphous alumina at about 300℃. This alumina is in a highly disordered metastable state, which can melt into the glass network more quickly and uniformly. This results in a glass network structure with higher symmetry and greater density, which can effectively block ion exchange, fundamentally reduce structural defects, and improve acid and alkali resistance.

[0034] A method for preparing acid and alkali resistant frit, used to prepare the above-mentioned acid and alkali resistant frit, includes the following steps: mixing the raw materials for the acid and alkali resistant frit, placing them in a furnace, heating them to the highest frit firing temperature of 1500~1560℃, holding them at that temperature for 30~40 minutes, then quenching them in water, crushing and ball milling the quenched frit, passing it through a 100~250 mesh sieve to collect the sieve material, drying it, and obtaining the acid and alkali resistant frit.

[0035] Excessively high firing temperatures or prolonged holding times can lead to significant boron volatilization or stratification. The B2O3 in boron-magnesium powder and zinc borate has high vapor pressure at high temperatures, and volatilization intensifies with longer firing times. Simultaneously, the surface melt becomes viscous due to B2O3 loss, while the lower layer becomes thinner due to B2O3 enrichment, resulting in severe chemical inhomogeneity. This leads to the localized precipitation of aluminum borate crystals after water quenching, creating weak points for corrosion. Holding at the maximum temperature for 30-40 minutes is for homogenization, but excessively long holding times can damage the glass network structure, causing excessive breakage of silicon-oxygen bonds. Glazes fired under these conditions are prone to crystallization devitrification, whitening, fogging, and orange-peel defects.

[0036] If the maximum firing temperature is too low or the holding time is too short, the reaction will be incomplete, resulting in a phase-separated structure. The melt cannot be homogenized, and B2O3 and SiO2 will not form a continuous network. Localized boron-rich and silicon-rich regions will coexist. This phase-separated structure has extremely poor chemical stability. The boron-rich phase is easily corroded by acid, and its acid resistance will decrease significantly. At the same time, the incomplete reaction will cause some raw materials to remain unmelted, resulting in raw material particles mixed in with the melt. The output is loose and easily turns into powder rather than glass particles after water quenching. This will lead to large fluctuations in moisture content during subsequent ball milling, increasing the difficulty of production control.

[0037] An acid and alkali resistant glaze, by mass parts, comprises: 6-10 parts kaolin, 10-26 parts quartz, 2-6 parts zinc oxide, and 53-87 parts of the above-mentioned acid and alkali resistant frit, wherein, in the chemical composition of the acid and alkali resistant glaze, zinc oxide is ≥2.2% by mass percentage of the oxide of the element.

[0038] In glaze formulations, the balance between acid and alkali resistant frit and quartz is crucial for both acid and alkali resistance. Excessive or insufficient amounts of either will result in a glaze that is either acid-resistant but not alkali-resistant, or alkali-resistant but not acid-resistant. The abundant silica in quartz and the acid-alkali resistant frit provides excellent acid resistance; the boron-oxygen tetrahedra formed by the frit exhibit good alkali resistance, and the alumina, zirconium oxide, and cerium oxide in the frit are also excellent acid and alkali resistant materials.

[0039] Kaolin mainly plays a suspending role in glazes. If the amount used is too low, the glaze will sink to the bottom; if the amount used is too high, the glaze slurry will be too viscous, and air bubbles will not be able to escape during glazing, resulting in defects such as pinholes on the glaze surface.

[0040] Zinc oxide provides good color development for glazes and ensures the pores of the glaze layer after polishing. If too little is used, the glaze surface will have too much color development and too many pores; if too much is used, the high activity of zinc oxide will reduce the acid and alkali resistance of the glaze layer.

[0041] Preferably, the quartz particle size is 8000~10000 mesh.

[0042] The quartz commonly used in glazes is 325 mesh. However, 325 mesh quartz particles are relatively large and unevenly distributed, creating micro-stress concentration points in the glaze layer after firing, and resulting in weak bonding with the glass phase interface. These interfaces and microcracks are the first channels for acid and alkali solutions to penetrate, accelerating corrosion over time. Using 8000-10000 mesh quartz allows for better melting and more complete reaction of the ultrafine powder, significantly reducing the porosity and microcracks of the glaze layer and forming a denser, continuous glass phase. For polished glazed tiles, higher density translates to stronger chemical durability and superior acid and alkali resistance.

[0043] A method for preparing an acid and alkali resistant glaze, comprising the following steps: mixing the raw materials for the acid and alkali resistant glaze, ball milling them, and passing the material through a 100-250 mesh sieve to obtain the sieve material, thereby obtaining the acid and alkali resistant glaze.

[0044] A method for preparing acid and alkali resistant glazed bricks, using the above-mentioned acid and alkali resistant glaze, includes the following steps: applying the acid and alkali resistant glaze to the surface of the brick blank, sending it into a kiln for firing, raising the temperature to the highest glaze firing temperature of 1140~1160℃, holding it at that temperature for 5~8 minutes; then cooling it, and after polishing and waxing, obtaining acid and alkali resistant glazed bricks.

[0045] Preferably, the firing temperature rise curve is as follows: room temperature - 600℃, heating time 17~19 minutes; 600~1050℃, heating time 8~9 minutes; 1050℃~the highest glaze firing temperature, heating time 4~5 minutes, holding at the highest glaze firing temperature for 6~7 minutes, with a total firing time of 35~40 minutes.

[0046] By utilizing the excellent low-temperature rapid firing adaptability of acid and alkali resistant glazes, a non-porous, highly dense polished glaze surface with excellent acid and alkali resistance can be formed under a rapid firing regime, which significantly improves production efficiency and reduces energy consumption.

[0047] Preferably, the cooling step is as follows: after firing, the temperature is reduced to 650°C for 5-8 minutes, and then naturally cooled to room temperature.

[0048] An acid and alkali resistant glazed tile is prepared by the above-mentioned preparation method, and the chemical corrosion resistance of the glaze is GLA grade and GHA grade.

[0049] The acid and alkali resistant glazed tiles prepared by this invention achieve GLA level resistance to low concentration acids and alkalis and GHA level resistance to high concentration acids and alkalis, meeting the AAAAA level requirements for chemical corrosion resistance in GB / T 45817-2025 "Ceramic Tiles for Consumer Product Quality Classification".

[0050] Examples 1-3 The raw materials for acid and alkali resistant frits are shown in Table 1 below: Table 1. Raw material list of acid and alkali resistant frit (parts by weight)

[0051] The firing temperature curve of the acid and alkali resistant frit is as follows: room temperature - 300℃, heating time 40 minutes; 300~1200℃, heating time 90 minutes; 1200~1530℃, heating time 30 minutes; 1530℃, holding time 32 minutes; then quenched in water, ball-milled, passed through a 100-mesh sieve to collect the sieve material, and dried to obtain the acid and alkali resistant frit.

[0052] Comparative Example 1 The difference from Example 1 is that the firing temperature curve of the frit is as follows: room temperature - 300℃, heating time 40 minutes; 300~1200℃, heating time 90 minutes; 1200~1560℃, heating time 30 minutes; 1560℃, holding time 50 minutes; then quenched in water, ball-milled, passed through a 100-mesh sieve to collect the sieve material, and dried to obtain acid and alkali resistant frit.

[0053] Comparative Example 2 The difference from Example 1 is that the firing temperature curve of the frit is as follows: room temperature - 300℃, heating time 40 minutes; 300~1200℃, heating time 90 minutes; 1200~1560℃, heating time 30 minutes; 1560℃, holding time 50 minutes; then quenched in water, ball-milled, passed through a 100-mesh sieve to collect the sieve material, and dried to obtain acid and alkali resistant frit.

[0054] Comparative Example 3 The difference from Example 1 is that the firing temperature curve of the frit is as follows: room temperature - 300℃, heating time 40 minutes; 300~1200℃, heating time 90 minutes; 1200~1500℃, heating time 30 minutes; 1500℃, holding time 20 minutes; then quenched in water, ball-milled, passed through a 100-mesh sieve to collect the sieve material, and dried to obtain acid and alkali resistant frit.

[0055] Example 4 Using the acid and alkali resistant frit from Example 1, the raw materials for the acid and alkali resistant glaze are shown in Table 2 below: Table 2 Raw material list of acid and alkali resistant glaze (parts by weight)

[0056] After mixing the raw materials for acid and alkali resistant glaze, the mixture is ball-milled in a ball mill and the material passing through a 100-mesh sieve is collected to obtain the acid and alkali resistant glaze. An acid- and alkali-resistant glaze is applied to the surface of a conventional brick blank using a glazing process. The specific gravity of the glaze is 1.83~1.88 g / cm³. 3 The glaze application rate is 470~478g / m². 2 The material is then placed in a kiln for firing. The firing temperature curve is as follows: room temperature to 600℃, heating time 18 minutes; 600~1050℃, heating time 8 minutes; 1050~1150℃, heating time 5 minutes; 1150℃, holding for 7 minutes; after firing, it is rapidly cooled to 650℃ for 5 minutes, and then naturally cooled to room temperature. After conventional polishing and waxing, acid and alkali resistant glazed tiles are produced and then packaged with film.

[0057] Example 5 The difference from Example 4 is that the acid and alkali resistant frit of Example 2 is used instead of the acid and alkali resistant frit of Example 1. The raw materials of the acid and alkali resistant glaze are shown in Table 2.

[0058] Example 6 The difference from Example 4 is that the acid and alkali resistant frit of Example 3 is used instead of the acid and alkali resistant frit of Example 1. The raw materials of the acid and alkali resistant glaze are shown in Table 2.

[0059] Comparative Example 4 The difference from Example 4 is that the acid and alkali resistant frit of Comparative Example 1 is used instead of the acid and alkali resistant frit of Example 1.

[0060] Comparative Example 5 The difference from Example 4 is that the acid and alkali resistant frit of Comparative Example 2 is used instead of the acid and alkali resistant frit of Example 1.

[0061] Comparative Example 6 The difference from Example 4 is that the acid and alkali resistant frit of Comparative Example 3 is used instead of the acid and alkali resistant frit of Example 1.

[0062] Comparative Example 7 The difference from Example 4 is that the amount of acid and alkali resistant frit used is reduced to 50 parts.

[0063] Comparative Example 8 The difference from Example 4 is that the amount of acid and alkali resistant frit is increased to 90 parts.

[0064] Comparative Example 9 The difference from Example 4 is that acid and alkali resistant frit is not used, and the raw materials of the acid and alkali resistant glaze are increased by 1.4 parts of cerium oxide, 4.2 parts of zirconium oxide, and 3.5 parts of aluminum hydroxide.

[0065] Comparative Example 10 The difference from Example 4 is that acid and alkali resistant frit is not used; instead, the raw materials of the acid and alkali resistant frit from Example 1 are directly added to the raw materials of the glaze.

[0066] Comparative Example 11 The difference from Example 4 is that 325-mesh quartz is used instead of 8000-mesh quartz, while the amount of quartz used is the same.

[0067] Comparative Example 12 The difference from Example 4 is that the amount of quartz (8000 mesh) is reduced to 8 parts.

[0068] Comparative Example 13 The difference from Example 4 is that the amount of quartz (8000 mesh) is increased to 30 parts.

[0069] Comparative Example 14 The difference from Example 4 is that zinc oxide is not added.

[0070] The chemical corrosion resistance was tested according to GB / T 45817-2025 "Ceramic Tiles for Quality Grading of Consumer Products". The test data for the examples and comparative examples are shown in Table 3 below: Table 3 Test Performance Table

[0071] The holding time of the frit in Comparative Example 1 at the highest frit firing temperature was too long, and the viscosity of the frit decreased significantly during the firing process, which reduced the resistance of the glazed bricks in Comparative Example 4 to high-concentration acid and high-concentration alkali corrosion.

[0072] The excessively high maximum melting temperature of the frit in Comparative Example 2 caused the viscosity to decrease and then increase during the frit firing process, resulting in severe phase separation and a deterioration in the corrosion resistance of the glazed brick in Comparative Example 5.

[0073] The holding time of the frit in Comparative Example 3 at the highest frit firing temperature was insufficient, and the glass phase of the frit contained white particles that did not melt during the frit firing process. This resulted in the glaze surface of the glazed tile in Comparative Example 6 having more pores and poorer resistance to acid and alkali corrosion.

[0074] Comparative Example 7: Due to insufficient use of acid and alkali resistant frit, even when the missing main components were supplemented in the raw materials of the glaze, the acid and alkali resistance was still insufficient.

[0075] Comparative Example 8 shows that due to the excessive amount of acid and alkali resistant frit, in which zirconium oxide is used as an opacifier, the glaze layer has poor transparency and its resistance to high concentrations of alkali is reduced.

[0076] Comparative Example 9 uses cerium oxide, zirconium oxide and aluminum hydroxide directly added to the glaze. Due to the lack of strong fluxes such as boron oxide and lithium oxide in the overall formula, the glaze sintering is poor, the pores of the glaze after polishing are extremely poor, and the acid and alkali resistance is reduced.

[0077] In Comparative Example 10, the raw material of acid and alkali resistant frit was used directly as the raw material for the glaze. The boron oxide raw material introduced into the raw material changed the pH balance of the glaze slurry, resulting in severe thixotropy and failure to meet the requirements of the glazing process. At the same time, since the raw material was not pre-reacted at high temperature, it was only simply mixed. During glaze firing, the reaction time was short and the temperature was uneven, which prevented the boron oxide from fully transforming from a layered structure to a tetrahedral three-dimensional network structure. The resulting glass network was loose and contained a large number of incompletely reacted glass phase regions. Zirconia failed to fully react and uniformly precipitate zirconium silicate microcrystals, and even existed in isolation as unreacted particles, forming structural weak points. This resulted in poor glaze surface smoothness, many pinholes, uneven crystal distribution, and a lack of a dense protective layer. Ultimately, the glaze surface was prone to cracking and leaving erosion sites, and the acid and alkali resistance decreased.

[0078] Comparative Example 11 uses conventional 325-mesh quartz instead of 8000-mesh quartz. During the firing process, the 325-mesh quartz cannot be completely melted. After polishing, the pores on the glaze surface will increase, and acid and alkaline liquids will corrode the glaze surface through the pores, resulting in poor chemical corrosion resistance of the glaze surface.

[0079] Comparative Example 12 shows that the acid resistance is reduced due to insufficient quartz content.

[0080] Comparative Example 13: Due to excessive use of quartz, which has a high melting point, the large amount of quartz introduced will cause the overall melting temperature of the glaze to be too high and the high-temperature viscosity to be too high. Gas cannot be discharged in the glaze layer, resulting in more and larger pores after polishing and a decrease in acid and alkali resistance.

[0081] In Comparative Example 14, due to the lack of zinc oxide, the glaze surface will have more pores after polishing. The more pores in the glaze surface, the more acid and alkali solutions will seep into the glaze layer along the pores and corrode it, thus reducing its resistance to high concentrations of acid and alkali. At the same time, the overall color of the glaze surface will be bluish and the transparency will be white.

[0082] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0083] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. An acid and alkali resistant frit, characterized in that, By mass, the raw materials include: 25-35 parts boron magnesium powder, 37-53 parts potassium feldspar, 1-3 parts zinc borate, 5-15 parts spodumene, 4-8 parts zirconium oxide, 1-3 parts cerium oxide, and 3-7 parts aluminum hydroxide; and by mass ratio, the total amount of boron magnesium powder and zinc borate is greater than 26% of the raw materials of the acid and alkali resistant ingot, and the ratio of the total amount of boron magnesium powder and zinc borate to the total amount of potassium feldspar and spodumene is 0.4-0.9:

1. In the chemical composition of the acid and alkali resistant ingot, by mass percentage of the oxides of the elements, boron oxide ≥ 8.4%, zinc oxide ≥ 0.4%, and cerium oxide ≥ 1%.

2. A method for preparing an acid and alkali resistant frit, characterized in that, The steps for preparing the acid and alkali resistant frit as described in claim 1 are as follows: after mixing the raw materials for the acid and alkali resistant frit, place them in a furnace, heat them to the highest frit firing temperature of 1500~1560℃, keep them at that temperature for 30~40 minutes, then put the materials into water for quenching, crush the quenched frit and ball mill it, pass it through a 100~250 mesh sieve to collect the sieve material, and dry it to obtain the acid and alkali resistant frit.

3. An acid and alkali resistant glaze, characterized in that, The raw materials, by mass percentage, include: 6-10 parts kaolin, 10-26 parts quartz, 2-6 parts zinc oxide, and 53-87 parts of the acid and alkali resistant frit as described in claim 1, and the acid and alkali resistant glaze contains, by mass percentage, zinc oxide ≥ 2.2% of the element oxide.

4. The acid and alkali resistant glaze according to claim 3, characterized in that: Quartz has a particle size of 8000~10000 mesh.

5. A method for preparing an acid and alkali resistant glaze, characterized in that, The method for preparing the acid and alkali resistant glaze according to claim 3 or 4 includes the following steps: mixing the raw materials of the acid and alkali resistant glaze, ball milling them, and passing the material through a 100-250 mesh sieve to obtain the sieve material, thereby obtaining the acid and alkali resistant glaze.

6. A method for preparing acid and alkali resistant glazed bricks, characterized in that, Using the acid and alkali resistant glaze as described in claim 3 or 4, the method includes the following steps: applying the acid and alkali resistant glaze to the surface of the brick blank, sending it into a kiln for firing, raising the temperature to the highest glaze firing temperature of 1140~1160℃, and holding it for 5~8 minutes; then cooling, and polishing and waxing to obtain acid and alkali resistant polished glazed bricks.

7. The preparation method according to claim 6, characterized in that, The firing temperature rise curve is as follows: room temperature to 600℃, heating time 17~19 minutes; 600~1050℃, heating time 8~9 minutes; 1050℃ to the highest glaze firing temperature, heating time 4~5 minutes, holding at the highest glaze firing temperature for 6~7 minutes, with a total firing time of 35~40 minutes.

8. The preparation method according to claim 6, characterized in that, The cooling process is as follows: after firing, the temperature is reduced to 650℃ for 5-8 minutes, and then allowed to cool naturally to room temperature.

9. An acid and alkali resistant glazed tile, characterized in that: Prepared by the preparation method according to any one of claims 6-8, the glaze has chemical corrosion resistance of GLA grade and GHA grade.